Composite coatings for corrosion protection of AISI 304 stainless steel - Shcholokova, Anastasiia (National Technical University "Kharkiv Polytechnic Institute", 2025)
Austenitic steels, especially AISI 304, are widely used because of their strength and corrosion resistance, but are subject to dangerous types of corrosion. Inhibitors and coatings are used for protection, but inhibitors are poorly understood under extreme conditions and coatings require refinement. A promising solution is composite coatings combining a matrix (polymers, metals, oxides) and a dispersed phase (carbides, nitrides, borides, oxides, carbon nanomaterials). They provide strength and chemical inertness. This paper gives a brief overview of the research relevance in the development and application of composite coatings for corrosion protection.
Keywords: stainless steel; corrosion protection; protective coatings